Effect of Supplementation of Capsaicin as a Natural Stimulant for the Immune System in Ross Broiler Chickens - Sanabria Naranjo, Fernando; Mendoza García, Mauricio (Spei Domus, 2013)
Capsaicin is the active substance contained in chili peppers.Research has been carried out on capsaicinoids in poultry to prevent salmonella problems. The worldwide trend to reduce antibiotics as growth promoters (agp’s) has led to increased research to replace them with natural alternatives, such as the use of capsaicinoids. The objective of our study was to evaluate the effect of the addition of capsaicinoids in concentrations of 10, 30 and 50 ppm administered during the first 16 days of breeding of both male and female Ross broiler chickens. The effect from capsaicinoid supplementation on the immune system of broilers was evaluated with respect to bronchitis, Gumboro and New Castle diseases. The zootechnical parameters measured were body weight, feed conversion, mortality, allometric study of the internal organs and immune response. None of the broilers stopped consuming their feed when it contained capsaicinoids. At the same time, no significant differences were found regarding feed conversion ratio and weight gain. New Castle disease antibody levels found through the Elisa test were higher in the vaccinated broilers; for Gumboro disease and bronchitis, higher antibody levels were found in unvaccinated broilers. We found a tendency for antibody levels to increase as capsaicinoid concentrations were increased in the broilers’ diet.